Pengembangan Buku Ajar Tematik Integratif Semua Mata Pelajaran Di Sekolah Dasar Islam - .., Sulistyowati (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2014)
Development of the fist class textbook using a thematic approach to integrative learning in Islamic primary school (SDI) based on the fact that the unavailability of special thematic textbook for students who attend school in Islamic institutions that accommodate all subjects including PAIand manners. The approach chosen thematic learning because students in the early grades still think holistically. They see something to make a whole, so that the thematic approach is the right approach to use.In this textbookdevelopment, developers use development methods in general, the planning, development, validation, testing, and dissemination. Development design model used is a model of Dick and Lou Carey. The results showed that the textbook class I by using thematic integrative learning approach has a level of effectiveness, effiiency, and attractiveness high. This is indicated by the test results are in good category according to a scale of 5 and an increase in student scores of 7.38. Thus, it can be said the development has contributedto the settlement of problems that arise in schools, especially on thematic integrative learning all subjects, including religion in class I. The product of this development can be disseminated to students who have the same characteristics.Keywords: Development, Textbook, Thematic Integrative Learning